Distribution of Potentially Toxic Elements in Sediments of the Subarnakhali River, Bangladesh: Ecological Risks Assessment (Journal of the Bangladesh Agricultural University, 2025)
There are major ecological and health risks associated with the accumulation of toxic metals in river sediments, particularly in regions where industrial and agricultural activities are prevalent. This study measured the concentrations of six toxic metals (Cr, Ni, Cu, Cd, Pb, and As) in the sediments of the Subarnakhali River using ICP-MS and evaluated the associated risks. The mean concentrations (mg/kg) of the toxic metals were as follows: Ni (41.01 ± 4.65) > Cu (29.01 ± 3.77) > Cr (20.18 ± 3.40) > Pb (17.59 ± 3.45) > Cd (1.29 ± 0.19) > As (1.18 ± 0.11). Notably, Ni and Cd levels exceeded the allowable limits set by sediment quality guidelines, indicating potential ecological concerns. Multivariate analyses (Pearson correlation, principal component analysis, and cluster analysis) revealed that Pb and As had both natural and anthropogenic origins, whereas Cu, Cr, and Ni were primarily derived from industrial sources. Pollution assessment indicated that the sediments were moderately to severely contaminated based on the geo-accumulation index (Igeo) and severely enriched (EF = 8.02). Moderate to high pollution levels were also reflected in the pollutant load index (PLI), modified contamination degree (mCD), and contamination degree (CD). Potential ecological risk evaluations (PER = 379.42 to 537.43) suggested significant threats, particularly from Cd. Although toxic unit (TU) values were below acute toxicity thresholds, the long-term presence of these metals could harm aquatic ecosystems and pose risks to human health. These findings underscore the urgent need for stricter regulation of industrial and agricultural discharges, improved waste management, and enhanced public awareness to prevent further contamination and protect the ecological integrity of the river.J Bangladesh Agril Univ 23(3): 455–467, 2025